2017
DOI: 10.31223/osf.io/utnz2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different frequencies and triggers of canyon filling and flushing events in Nazaré Canyon, offshore Portugal

Abstract: Submarine canyons are one of the most important pathways for sediment transport into ocean basins. For this reason, understanding canyon architecture and sedimentary processes has importance for sediment budgets, carbon cycling, and geohazard assessment. Despite increasing knowledge of turbidity current triggers, the down-canyon variability in turbidity current frequency within most canyon systems is not well constrained.NewAMS radiocarbon chronologies from canyon sediment cores illustrate significant variabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
(221 reference statements)
0
8
1
Order By: Relevance
“…If more than half of the sampling points had adjacent canyons, we assigned that interval to have a canyon (24%). Though this procedure resulted in averaging of terrestrial parameters and does not assign particular rivers to particular canyons, we believe that averaging is justified by the paleogeographic uncertainty concerning specific river‐canyon connections (Fagherazzi et al, ), by the offset of canyons by transform faulting (Nagel et al, ), and by the possibility for long distance littoral transport of sediment delivered by rivers into nearby active canyons (Allin et al, ; Covault & Fildani, ). To assess the effects of this approach, we also conducted several sensitivity analyses in which we varied the spatial extent of averaging and the method of assigning canyon presence versus absence (see section 3).…”
Section: Methodsmentioning
confidence: 99%
“…If more than half of the sampling points had adjacent canyons, we assigned that interval to have a canyon (24%). Though this procedure resulted in averaging of terrestrial parameters and does not assign particular rivers to particular canyons, we believe that averaging is justified by the paleogeographic uncertainty concerning specific river‐canyon connections (Fagherazzi et al, ), by the offset of canyons by transform faulting (Nagel et al, ), and by the possibility for long distance littoral transport of sediment delivered by rivers into nearby active canyons (Allin et al, ; Covault & Fildani, ). To assess the effects of this approach, we also conducted several sensitivity analyses in which we varied the spatial extent of averaging and the method of assigning canyon presence versus absence (see section 3).…”
Section: Methodsmentioning
confidence: 99%
“…Their volume suggests that these mega‐beds are mostly sourced from distinctly larger scale failures on the Squamish Delta (see section on Sources of flows ). Previous work has suggested that submarine canyon systems experience two scales of event, which either fill or flush the canyon and may be related to different triggering mechanisms (Arzola et al ., ; Allin et al ., ). Similar bimodality of flows occurs in this fjord‐delta system.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in flow frequency are also key for understanding fundamental flow behaviour; such as how often flows erode and accelerate (ignite; Parker, ), or deposit sediment and dissipate, and the length scales over which such changes occur. It has also been proposed that turbidity currents in larger submarine canyon fed systems are strongly bimodal, such that most events are canyon filling, whilst only a few much larger flows flush sediment out of canyons (Arzola et al ., ; Allin et al ., ). More generally, flow frequency has important implications for the tempo of organic carbon and nutrient transport into deeper water (Galy et al ., ) and the physical disturbance of benthic ecosystems (Paull et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phenomena like liquefaction of mud usually only occur up to 25 days from deposition (Mehta, 2014), so are unlikely to happen under a turbidity current unless the frequency of large events is very high (cf. Gutierrez-Pastor et al, 2009;Allin et al, 2016).…”
Section: Mud Volume Flow Behaviour and Depositional Processesmentioning
confidence: 99%